Perancangan Sistem Informasi Client-Server Pencarian Tugas Akhir, Riset, dan Buku Berbasis Wireless Aplication Protocol (WAP) - Haryono Leo Rikardo; Munifah -; Wachid Ahmad Jauhari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2013)
Wireless Internet Media is wireless internet access which marks that the technology has become more advanced. Nowadays, mobile phones are not only used for communication but, can also accessing internet. Moreover, the discovery of the Wireless Application Protocol (WAP) enables a mobile phone (mobile device) to access a lot of information, one of which is information about the Digital Library (Digilib). Digilib are inseparable part of the students, because it provides a collection of informations that can be used by the students as a reference to support lectures in particular and education in general. Therefore, a student or those who come from the education world inevitably will use this Digilib services. Many Digilibs are supported by web-based services. However, not all users can access Digilib easily because of limited personal internet access, so this thesis gives a solution to build Digilib applications based on Wireless Application Protocol (WAP-based). The result of this research is to produce a design of Digilib with a variety of features, such as a detailed book review, book search, and a link to download the books. This application was built using the Wireless Markup Language (WML) as programming language and PHP using MySQL database.